Persuasão no discurso publicitário de instituições bancárias no Brasil - Delgado, Tereza Cristina Teixeira (2017)
The analysis of the advertising discourse of financial institutions is the objective of the present research, which aims to scale the power of persuasion of the commercial banks through the media relationship with their clients and users. For this, the content of five advertising pieces sponsored by the largest banks established in Brazil, based on their economic dominance in the market, is based on the content. The texts, in the form of videos, transmitted through digital television and platform, were chosen in a random manner, within a certain period. The basis for achieving the objective of the research was the rhetorical studies, with a view to identifying in the universe of analysis, the presence of the strategies of ethos and discursive pathos, based on Aristotle, brought to modernity through Perelman. It was also proposed to classify the texts in the form of advertising modulation, according to Carrascoza's conception, in order to identify the predominance of Apollonian or Dionysian modulation in the discourse of bank advertising, but not before confronting such strategies with the perception of Charaudeau On the content of the mediatic discourse. Almeida was the theoretical basis used to know and recognize the specific discursive strategies of financial institutions, according to the peculiarities of the service rendering sector. A gender cut was also worked out with the aim of observing the representation of the image of the woman (client or bank) in the discourse of the banks. Finally, counterfacts were presented to the arguments of financial institutions, based on the perspective of consumers and employees dissatisfied with the service and / or institutional relationship, manifested through statistical data released by the Central Bank of Brazil and by consumer protection agencies, As well as denunciations made by trade union entities.